Teaching English Grammar and Maintaining Students’ Learning Motivation through Humour Stories - Asfi Aniuranti; Yasinta Wulandari; M. Happy Nur Tsani (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
English structure is one of the principal elements considered problematic by many students. Therefore, every teacher is always encouraged to use the effective teaching ways. One of the proposed ways in teaching English grammar is using media like humour stories. As suggested teaching media, humour stories require an examination. Therefore, this research attempts at finding out the effectiveness of humour stories to teach grammar and maintaining students’ learning motivation. The method employed was quasi-experimental research. The instruments used were a test, questionnaire, and field note. The participants of this study were two classes of English Language Teaching Department. The students learnt some grammar topics such as past simple, present perfect, passive voice of past tense, passive voice of present perfect, passive voice of present simple, passive voice of present continuous, passive voice of present future, relative clause, and noun clause. The results reveal that humour is an effective teaching media for grammar. The significance of 2-tailed (0.035) was lower than 0.05. There is a significant difference between control and experimental group. Furthermore, the result of the questionnaire shows that the usage of humour positively influenced the learners’ motivation. The observation results also reveal that the teaching atmosphere in the experimental class is getting better in each meeting.